Phenotypes of craniofrontonasal syndrome in patients with a pathogenic mutation in EFNB1. - van den Elzen, M; Twigg, SR; Goos, J; Hoogeboom, A; van den Ouweland, A; Wilkie, A; Mathijssen, I (2014)
Craniofrontonasal syndrome (CFNS) is an X-linked developmental malformation, caused by mutations in the EFNB1 gene, which have only been described since 2004. A genotype-phenotype correlation seems not to be present. As it is of major importance to adequately counsel patients with EFNB1 mutations and their parents, and to improve diagnosis of new patients, more information about the phenotypic features is needed. This study included 23 patients (2 male, 21 female) with confirmed EFNB1 mutations. All patients underwent a thorough physical examination and photographs were taken. If available, radiological images were also consulted. Hypertelorism, longitudinal ridging and/or splitting of nails, a (mild) webbed neck and a clinodactyly of one or more toes were the only consistent features observed in all patients. Frequently observed phenotypic features were bifid tip of the nose (91%), columellar indentation (91%) and low implantation of breasts (90%). In comparison with anthropometric data of facial proportions, patients with CFNS had a significantly different face in multiple respects. An overview of all phenotypic features is shown. Patients with EFNB1 mutations have a clear phenotype. This study will facilitate genetic counseling of parents and patients, and contribute to the diagnostic and screening process of patients with suspected CFNS.